Hypothesising that salts of iodine, strontium and caesium reverse ageing induced by nuclear radiation. (1st January 2013) - Braverman, Eric R.; Baker, Robert J.; Dushaj, Kristina; Lau, Vivian; Polanin, Margaret; Lohmann, Raquel; Blum, Kenneth; Loeffke, Bernard
Radiation accelerates ageing, producing telomere shortening, metabolic ageing, cell apoptosis, immunological decline, mitochondrial damage, free radical damage and oxidative stress. Salts of iodine, strontium and caesium may reverse ageing induced by nuclear radiation. The American Thyroid Association (ATA) has established that potassium iodide (KI) needs to be accessible to those within 50 miles of nuclear reactors. Despite ATA recommendations, if you distribute KI at the time of explosion, it may not be effective; thus, it is a preventive measure, not a tertiary treatment. KI treatment is most successful when used prior to radioactive iodine exposure. Weekly supplementation of KI reduces hypothyroidism and thyroid nodules; strontium carbonate (SrCO3) reduces osteopenia and inadequate bone development; and caesium chloride (CsCl) reduces brain cell apoptosis and anxiety. Low doses of radiation may result in hormesis and improved health. A radiation cleanup plan with further investigation could be implemented as a preventive measure.